2023
DOI: 10.1097/md.0000000000033944
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and its associated factors among pregnant women in Ilala Municipality - Tanzania: Analytical cross-sectional study

Abstract: Anaemia during pregnancy is still 1 of the leading causes of maternal and neonatal mortality in low and middle-income countries. Initiatives to address this need evidence on trends and their relevant factors, as they vary from 1 area to another. This study determined the prevalence of anemia and its associated factors among pregnant women in Ilala, Tanzania. This community-based, analytical cross-sectional study was conducted in April 2022 involving 367 randomly selected pregnant women. An interviewer-administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Anemia during pregnancy is found to increase in the third trimester, during pregnancy the body requires more iron to produce hemoglobin due to fetal growth, therefore consuming adequate food diversity is very important. In this study, pregnant women in their third trimester were found to have poorer appetite, consume less dark vegetables and consume less milk than mothers in their second trimester (28).…”
Section: Discussionmentioning
confidence: 68%
“…Anemia during pregnancy is found to increase in the third trimester, during pregnancy the body requires more iron to produce hemoglobin due to fetal growth, therefore consuming adequate food diversity is very important. In this study, pregnant women in their third trimester were found to have poorer appetite, consume less dark vegetables and consume less milk than mothers in their second trimester (28).…”
Section: Discussionmentioning
confidence: 68%
“…According to the World Health Organization (WHO), anaemia is a condition in which the haemoglobin concentration within the red blood cells are lower than normal and consequently their oxygen carrying capacity is insufficient to meet the physiological demands of the body ( 12 , 13 ). This results in symptoms such as; body weakness, fatigue, dizziness, palpitations and shortness of breath ( 13 , 14 ). In 2019, the prevalence rates of anaemia was estimated at 29.9% among women of reproductive ages (WRA) and 36.5% in pregnant women ( 15 ).…”
Section: Introductionmentioning
confidence: 99%